EVOLUTION OF THE TETHYS HIMALAYA CONTINENTAL SHELF DURING MAASTRICHTIAN TO PALEOCENE (ZANSKAR, INDIA) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The results of several—year stratigraphic researches on the Northwestern Himalaya Late Cretaceous—Early Tertiary succession are here presented. New biostratigraphic data allowed to recognize several benthic foraminiferal assemblages in five measured stratigraphic sections and to reconsider the position of the Cretaceous—Tertiary boundary. Refined chronostratigraphic calibration and assessment of sedimentation rates were obtained through correlation between benthic and planktonic biozones. Petrographical analysis of sandstones allowed to tentatively put forward a sedimentological model, to give rough estimates for temperatures of anchimetamorphic deformation in the different thrust sheets of the Tethys Himalaya zone and to shed new light on the genesis of superstable and supermature quartzarenites. Integrated sedimentological—petrographical studies allowed to distinguish at least three depositional sequences separated by major unconformities in the previously undifferentiated succession, and to put further constraints to the dating of the India—Asia collision.
Keywords: Himalaya; India; Cretaceous; Paleocene; Stratigraphy; Foraminifera; Sandstone petrography; Anchimetamorphism; Sea—level changes; Passive margin.